Roles of Phosphate in Skeleton - Michigami, Toshimi; Ozono, Keiichi (Frontiers in Endocrinology, 2019)
Phosphate is essential for skeletal mineralization, and its chronic deficiency leads to rickets and osteomalacia. Skeletal mineralization starts in matrix vesicles (MVs) derived from the plasma membrane of osteoblasts and chondrocytes. MVs contain high activity of tissue non-specific alkaline phosphatase (TNSALP), which hydrolyzes phosphoric esters such as pyrophosphates (PPi) to produce inorganic orthophosphates (Pi). Extracellular Pi in the skeleton is taken up by MVs through type III sodium/phosphate (Na+/Pi) cotransporters and forms hydroxyapatite. In addition to its roles in MV-mediated skeletal mineralization, accumulating evidence has revealed that extracellular Pi evokes signal transduction and regulates cellular function. Pi induces apoptosis of hypertrophic chondrocytes, which is a critical step for endochondral ossification. Extracellular Pi also regulates the expression of various genes including those related to proliferation, differentiation and mineralization. In vitro cell studies have demonstrated that an elevation in extracellular Pi level leads to the activation of fibroblast growth factor receptor (FGFR), Raf/MEK (mitogen-activated protein kinase/ERK kinase)/ERK (extracellular signal-regulated kinase) pathway, where the type III Na+/Pi cotransporter PiT-1 may be involved. Responsiveness of skeletal cells to extracellular Pi suggests their ability to sense and adapt to an alteration in Pi availability in their environment. Involvement of FGFR in the Pi-evoked signal transduction is interesting because enhanced FGFR signaling in osteoblasts/osteocytes might be responsible for the overproduction of FGF23, a key molecule in phosphate homeostasis, in a mouse model for human X-linked hypophosphatemic rickets (XLH). Impaired Pi sensing may be a pathogenesis of XLH, which needs to be clarified in future.